Ipertensione arteriosa, continuum cardiovascolare e ruolo clinico dei sartanii - Destro, Maurizio (Farmeconomia. Health economics and therapeutic pathways, 2011)
The cardiovascular and cardiorenal continuum comprises the transition from cardiovascular risk factors to endothelial dysfunction and atherosclerosis, to chronic congestive heart failure, and-stage renal disease or premature death. RAAS (renin-angiotensin-aldosterone system) is involved in all steps along this pathway. Data from clinical studies involving valsartan and other ARBs provide evidence of the reduction of risk of cardiovascular events, and end-organ damage in the heart, kidneys and brain. This paper summarizes the status on research of ARBs based on clinical trials and regulatory approval.